Applying in vitro-produced embryos and sexed sperm to dairy cattle reproduction - Rasmussen, Sara-Lesley, author; Seidel, George E., Jr., advisor; Graham, James K., committee member; McCue, Patrick M., committee member (Colorado State University. Libraries, 2011)
This study compared the pregnancy rates between embryo transfer of bovine embryos produced in vitro with sexed vs control sperm and artificial insemination (AI) using sexed and unsexed sperm. Cleavage rates for oocytes fertilized with sexed vs control sperm were not different for two of the three bulls used, but were lower (p < 0.05) for the third bull sexed (44%) vs control sperm (70%). There were fewer transferable blastocysts produced per oocyte with sexed sperm (9-19%) than for unsexed sperm (18-26%); (p < 0.05). All cows were on an Ovsynch program to synchronize ovulation. Respective 60 d pregnancy rates at two Colorado dairies were as follows: control AI (43%, n=88; 43%, n=44); AI with X-sorted sperm (34%, n=82; 34%, n=62); embryo transfer (ET) with in vitro-produced (IVP) embryos using unsexed sperm (22%, n=68; 21%, n=39); and ET with IVP embryos using sexed sperm (7%, n=72; 37%, n=40). The pregnancy rate (day 60) for AI using sexed sperm was 78% of that of control sperm. ET pregnancy rates were generally lower than AI rates. At one dairy, abortions between days 32 and term were higher for X-sort ET pregnancies (79% n=14) than for AI control pregnancies (20% n=40); (P < 0.001). However, the other dairy experienced only a 12%, (n=17) abortion rate for transferred embryos produced from X-sorted sperm. The sex ratio of calves was similar to previous studies for AI with control sperm (52% bull calves, n=50), AI with X-sorted sperm (12% bull calves, n=40); ET with IVP embryos using unsexed sperm (50% bull calves, n=18); and ET with IVP embryos using sexed sperm (11% bull calves, n=18). Findings from this experiment indicate that embryo production with sexed sperm is not successful enough to be applied to large-scale dairies that already have successful breeding programs in place.
Keywords: assisted reproduction technologies; dairy cattle fertility; embryo transfer; IVF; pregnancy rates; sexed sperm